The Myth of the Equiangular Triangle for Identification of Sacral Hiatus in Children Disproved by Ultrasonography. Issue 3 (1st May 2013) - Kim, Min-Soo; Han, Kyung-Hwa; Kim, Eun Mi; Jeong, Seung Ho; Lee, Jeong-Rim
Abstract : Background and Objectives: A triangle formed by the sacral hiatus and posterior superior iliac spines (PSISs) has been known as equiangular and has been proposed as a way to help identify the sacral hiatus for a caudal block. In children, however, no feasibility study of this triangle has been performed. We compared the expected sacral hiatus obtained from the equiangular triangle method and the real sacral hiatus confirmed by ultrasound. Methods: Eighty children (aged 0.5–72 months) were placed in the left lateral decubitus position in full hip flexion. The vertex of an equiangular triangle formed inferior to PSISs was considered as the expected sacral hiatus by classic bony landmarks. The real sacral hiatus was identified by ultrasound. The angle formed by the 2 lines connecting each PSIS and the real sacral hiatus (angle &θ) was also measured. The distances between the midpoint of PSISs and expected sacral hiatus (distance E ) and real sacral hiatus (distance R ) were measured and compared. Results: The angle &θ was greater than 60 degrees in all children (79.3 [9.3] degrees) and negatively correlated with age younger than 1 year. Distance R (3.5 [1.1] cm) was significantly shorter than distance E (4.9 [1.2] cm) ( P < 0.001). The distance R positively correlated with age, weight, height, and the distance between the PSISs. Conclusions: In children, using the equiangular triangle to identify the sacral hiatus may be inappropriate because the actual triangle formed by the sacral hiatus and PSISs is not equiangular.